Improvement in cognitive function in young people with bipolar disorder: Results from participants in an 18-month randomised controlled trial of adjunctive psychotherapy. (March 2020) - Porter, Richard J; Inder, Maree; Douglas, Katie M; Moor, Stephanie; Carter, Janet D; Frampton, Christopher MA; Crowe, Marie
Objective: To examine the effects of 18 months of intensive stabilisation with medication management and Interpersonal and Social Rhythm Therapy or Non-specific Supportive Clinical Management on cognitive function in young people with bipolar disorder. Determinants of change in cognitive function over the 18 months of the trial were also examined. Method: Patients aged 15–36 years with Bipolar I Disorder, Bipolar II Disorder and Bipolar Not Otherwise Specified were recruited. From a battery of cognitive tests, change scores for pre-defined domains of cognitive function were created based on performance at baseline and follow-up. Change was compared between the two therapy groups. Regression analysis was used to determine the impact of a range of clinical variables on change in cognitive performance between baseline and follow-up. Results: One hundred participants were randomised to Interpersonal and Social Rhythm Therapy ( n = 49) or Non-specific Supportive Clinical Management ( n = 51). Seventy-eight patients underwent cognitive testing at baseline and 18 months. Across both groups, there were significant improvements in a Global Cognitive Composite score, Executive Function and Psychomotor Speed domains from baseline to 18 months. Lower scores at baseline on all domains were associated with greater improvement over 18 months. Overall, there was no difference between therapies in change in cognitive function, either in a global composite score or change in domains. Conclusion: While there was no difference between therapy groups, intensive stabilisation with psychological therapy was associated with improved cognitive function, particularly in those patients with poorer cognitive function at baseline. However, this was not compared with treatment as usual so cannot be attributed necessarily to the therapies.